Study on the Impact of ESG Disclosure Quality on Corporate Value - Yang, Jie (Transactions on Economics, Business and Management Research, 2024)
This study examines the impact of ESG disclosure quality on firm value. This paper delves into the definition and assessment methods of ESG disclosure quality, as well as the mechanism of its impact on corporate value. It is found that high-quality ESG disclosure can have a positive impact on corporate value by reducing information asymmetry, enhancing corporate reputation, optimising risk management and promoting sustainable development. However, the assessment of ESG disclosure quality still faces challenges such as inconsistent standards and insufficient comparability. In addition, there are industry and regional differences in the impact of ESG disclosure quality on corporate value. The study also demonstrates how ESG disclosure quality affects firm value in practice by analysing the cases of Apple, Novo Nordisk and Alibaba. Finally, the study provides recommendations for firms, regulators, and investors to promote improved ESG disclosure practices and sustainable growth in firm value.